The implementation of the 'Testing of Phonological Skills (TOPS)' tool: a computer-based phonological analysis algorithm. - Armostis, Spyros; Petinou, Kakia; Kyprianou, Anna (Clinical Linguistics & Phonetics, 2023)
A computer-based algorithm was used for phonological analysis of Cypriot Greek (CG) word productions elicited from a sample of typically developing (TD) CG-speaking children. Specific focus was on (a) creating a complete CG phonetic and phonological test; (2) implementing a novel computer-based algorithm in the analysis of selected speech stimuli from CG-speaking TD children; and (3) examining independent and relational speech patterns based on the computer-based algorithm. The probe word list consisted of 182 target words and included all CG consonants in all word positions. Normative data were collected on a representative sample of 20 TD CG-speaking children aged 3;0 to 6;0 years. Productions were phonetically transcribed and inserted into the computer algorithm for automatic data reduction of measurable dependent variables including the percentage of consonants correct (PCC), phonetic inventory size (PIS), word-initial onset deletion (IOD), and Regressive Assimilation (RASS). Correlation analyses revealed significant interactions among phonetic and phonological patterns as well as predictive relationships of PCC and segmental word-position. The implementation of this specific probe word list permitted a homogeneous and inclusive sampling analysis. Participants presented specific developmental trajectories of segmental and phonological patterns as a function of age.